2017
DOI: 10.9790/3013-07020189110
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Primary Care Physicians Regarding Common Dermatological Disorders in Abha City, Kingdom of Saudi Arabia

Abstract: ABSTRACT:-Background:-Majorityof skin diseases are not life threatening, but the psychological effects of relativelyminor skin abnormalities can often cause more distress to the patients than other more serious medical disorders. As medical knowledge expands, family physicians face an ever-increasing challenge in diagnosis and treatment of skin disorders.Objectives:To assess knowledge, attitudes and practice (KAP) among primary health care providers (PHCP) in Abha City regarding Common dermatological problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 20 publications
2
20
3
Order By: Relevance
“…We think that the reason for this is that the majority of our participants were either uneducated or in primary education level, and their knowledge about hepatitis B and C was not satisfactory. Our result is consistent with other study conducted in Kingdom of Saudi Arabia [17]. New studies indicated that there was very poor knowledge about sexually transmitted diseases [18,19].…”
Section: Discussionsupporting
confidence: 83%
“…We think that the reason for this is that the majority of our participants were either uneducated or in primary education level, and their knowledge about hepatitis B and C was not satisfactory. Our result is consistent with other study conducted in Kingdom of Saudi Arabia [17]. New studies indicated that there was very poor knowledge about sexually transmitted diseases [18,19].…”
Section: Discussionsupporting
confidence: 83%
“…Most students had good knowledge and positive attitudes toward scabies and precautions against it. Personal hygiene of the students in our study was better than that reported from some developing countries (4,17,24). Al-Zahrani et al (24) showed a low-knowledge of the Saudi Arabia-Family Physicians regarding the Scabies.…”
Section: Discussioncontrasting
confidence: 61%
“…Personal hygiene of the students in our study was better than that reported from some developing countries (4,17,24). Al-Zahrani et al (24) showed a low-knowledge of the Saudi Arabia-Family Physicians regarding the Scabies. Binti Mohd Yusof et al (5) in Indonesia reported a moderate to good level of knowledge, attitude, and health behaviors for scabies prevention.…”
Section: Discussioncontrasting
confidence: 61%
“…Dentists and physicians working in secondary or tertiary care hospitals were excluded. According to studies that examined the knowledge of scabies diagnosis and treatment, the prevalence of satisfactory knowledge (≥75%) of scabies or other dermatologic diseases ranged between 8.6% in Saudi Arabia[ 21 ] and 36% in Pakistan. [ 17 ] Assuming a satisfactory knowledge of 15–20% with two-sided confidence limits of 5%, 182–224 physicians would be required, using 80% power level and 95% two-sided significance level.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has been observed that the majority of primary health care physicians had insufficient knowledge to manage common skin disorders. [ 21 ] The objective of the current study was to evaluate the knowledge of primary health care physicians about scabies diagnosis and management, as well as the factors influencing such knowledge.…”
Section: Introductionmentioning
confidence: 99%